2017
DOI: 10.1111/pre.12167
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure among cultivars of Saccharina japonica currently farmed in northern China

Abstract: Close to 50% of the annual production of the brown alga Saccharina japonica, about 2 million tons (fresh weight), is produced through farming in Shandong province, China, principally around Rongcheng. Under artificial selection for phenotypic traits (e.g. color, blade length) cultivated strains (cultivars) face the problems of inbreeding depression, which can be caused by the close relationships of the parental plants. Hence, in an attempt to evaluate genetic variations and relationships among cultivars, 15 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…The genetic diversity of the farmed and spontaneous populations was consistent with those detected in the previous studies (Li et al, 2017;Shan et al, 2017;Zhang et al, 2017). Interestingly, the subtidal spontaneous populations exhibited lower genetic diversity than the farmed populations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The genetic diversity of the farmed and spontaneous populations was consistent with those detected in the previous studies (Li et al, 2017;Shan et al, 2017;Zhang et al, 2017). Interestingly, the subtidal spontaneous populations exhibited lower genetic diversity than the farmed populations.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, the three farmed cultivars were demonstrated to be genetically close to each other. As was suggested and revealed in our previous studies, mixing among different cultivars were most likely caused by sharing of refrigerated seawaters during seedling production in the hatchery (Shan et al, 2011;Li et al, 2017). The result was the homogenization of genetic composition and agronomical features of the cultivars.…”
Section: Discussionmentioning
confidence: 53%
“…Across the 13 Saccharina cultivars examined in this study, we observed that the highest He and Ho value is 0.295, which is lower than natural kelp population in Japan and Russia (Zhang et al, 2017). However, another study showed that the genetic diversity of cultivars group was higher than the natural kelp populations (Li et al, 2017). The AFLP analysis of cultured and wild population of kelp in Dalian coast showed that the level of genetic variation of two kinds of population has no significant difference (Wang, 2009).…”
Section: Genetic Diversitymentioning
confidence: 51%
“…[8][9][10] However, several Asian cultivars suffer from inbreeding depression, due to continuous ''selfing'' and limited crossbreeds from a restricted germplasm base. 11 There is a general trend of decreasing abundance of several native kelp species, including S. latissima, at their southern distributional range limits and increasing abundance in other parts of their distribution, mainly northward. 4,12,13 The founder effect of postglacial colonization in northern S. latissima populations suggests a lower intraspecific genetic diversity compared with populations from the southern range of distribution.…”
Section: Introductionmentioning
confidence: 99%